The Use of Visual Media in Teaching Writing - Suhartono, Suhartono; Laraswati, Iranada (Universitas Nusantara PGRI Kediri, 2016)
Writing is the difficult skill in learning English. To make students get the idea in writing easily the teacher should be creative and innovative. The Application of visual media can help students get idea easily. This research aimed at knowing the application of visual media and the students’ responses in teaching writing to eleventh grade students of SMAMuhammadiyah Kediri.This qualitative research took place in SMAMuhammadiyah Kediri. The subject of this research was the eleventh grade students that consist of 17 male and 15 female students. In order to collect the data , observation, interview, questionnaire and the documentation were used. The application of visual media helped the students write easily. The teacher applied visual media to help the students write good sentences.The theme of the material is narrative text and the teacher applied picture series. The activity was devided into three steps (pre,whilst,post) start from make a simple sentence based on the picture series then compose a paragraph based on the simple sentences. By using visual media application in teaching writing the students gave good responses. They paid attention to the teacher’s explanation very well anddidthe task one by one. The students got more vocabulary, creativity in writing process. It deals with 67.76% students answered yes and 32.24% students answered no. It can be concluded that visual media application in teaching writing helps the students write easily as it helps the students to be more creative in finding the ideas and developing vocabulary. So it is suggested to the English teacher to improve the material, use this media in teaching other skills and. For the further researcher it is hoped that this research can give more information and contribution in conducting similar topic of discussion.